Blindsight in monkeys. - Cowey, A; Stoerig, P (1995)
Blindsight, the visually evoked voluntary responses of patients with striate cortical destruction that are demonstrated despite a phenomenal blindness, has attracted attention from neuroscientists and philosophers interested in problems of perceptual consciousness and its neuronal basis. It is assumed to be mediated by the numerous extra-geniculostriate cortical retinofugal pathways whose properties are studied primarily in monkeys. Like patients with blindsight, monkeys with lesions of the primary visual cortex can learn to detect, localize and distinguish between visual stimuli presented within their visual field defects. Although the patients deny seeing the stimuli they can nevertheless respond to (by forced-choice guessing) in their phenomenally blind fields, it is not known whether the monkeys experience the same absence of phenomenal vision. To determine whether they too have blindsight, or whether they actually see the stimuli in their field defects, monkeys who showed excellent detection in tasks where a visual stimulus was presented on every trial, albeit at different positions, were tested in a signal-detection task in which half the trials were blank trials, with no visual stimulus. They classified the visual stimuli presented in the field defect as blank trials, demonstrating, like patients, blindsight rather than degraded real vision.